Translation Techniques and Equivalence of Cultural Terms in Karisma Event Nusantara Magazine - Krisnayanti, Ni Kadek Rai; Dewi, Putu Chrisma; Kamayana, I Gusti Nyoman Putra (LPPM Universitas Dhyana Pura, 2025)
This study examines translation techniques and equivalence strategies in the English translation of cultural content in Karisma Event Nusantara Magazine, a bilingual publication issued by the Ministry of Tourism and Creative Economy of Indonesia. A descriptive qualitative method was employed in this study. The data were taken from the 2023 edition of the magazine, which presented the content in both Indonesian and English. Data collection was conducted using a note-taking technique, with cultural terms selected through purposive sampling. The analysis employed Molina and Albir’s (2002) framework of translation techniques and Newmark’s (1988) theory of semantic and communicative equivalence. Results showed that 12 out of 18 translation techniques were identified, with adaptation, calque, description, established equivalent, and literal translation as the most frequent (4 data each). Other techniques include borrowing (3), generalization (2), modulation (3), amplification (1), linguistic compression (1), substitution (1), and transposition (3). For equivalence, 19 instances of semantic equivalence and 15 of communicative equivalence were found. These findings demonstrate the strategies used to preserve cultural meaning while ensuring clarity for international audiences.